Pengaruh Inflasi, Pengangguran, Modal Manusia, dan Investasi Terhadap Pertumbuhan Ekonomi Seluruh Provinsi di Pulau Jawa Tahun 2020-2021 - Bagas Megondaru; Maulidyah Indira Hasmarini (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Economic growth is an important indicator to see the success of a country's development. The economic growth of each province in Java Island in 2020-2021 has experienced fluctuations caused by several economic factors. This study aims to estimate the effect of inflation, unemployment rate, human capital, and investment on economic growth in all provinces in Java Island in 2020-2021 using panel data regression using the Fixed Effects Model (FEM) approach. The results of this study indicate that, taken together, all the independent variables have a significant effect on unemployment. Partially, inflation and human capital each have a positive effect on economic growth, while the unemployment rate and investment have no effect on economic growth.